2001
DOI: 10.1080/106351501753328820
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Evolution of Dioecy from Monoecy in Siparunaceae (Laurales)

Abstract: Abstract.-Siparunaceae comprise Glossocalyx with one species in West Africa and Siparuna with 65 species in the neotropics; all have unisexual owers, and 15 species are monoecious, 50 dioecious. Parsimony and maximum likelihood analyses of combined nuclear ribosomal ITS and chloroplast trnL-trnF intergenic spacer sequences yielded almost identical topologies, which were used to trace the evolution of the two sexual systems. The African species, which is dioecious, was sister to all neotropical species, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
75
0
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(79 citation statements)
references
References 36 publications
2
75
0
2
Order By: Relevance
“…65 spp.) distributed in Central and South America (Renner and Hausner 1997;Renner and Won 2001) are poorly understood embryologically. In a previous paper (Kimoto and Tobe 2001), we presented a literature review of embryological features of Laurales (comprising seven families including Siparunaceae), and suggested that 16 embryological characters (e.g., mode of cytokinesis in the microspore mother cell, anther dehiscing mode, number of integuments) are diversified within the order and are likely to be useful in discussion of morphology-based relationships among and within the seven lauralean families.…”
Section: Introductionmentioning
confidence: 99%
“…65 spp.) distributed in Central and South America (Renner and Hausner 1997;Renner and Won 2001) are poorly understood embryologically. In a previous paper (Kimoto and Tobe 2001), we presented a literature review of embryological features of Laurales (comprising seven families including Siparunaceae), and suggested that 16 embryological characters (e.g., mode of cytokinesis in the microspore mother cell, anther dehiscing mode, number of integuments) are diversified within the order and are likely to be useful in discussion of morphology-based relationships among and within the seven lauralean families.…”
Section: Introductionmentioning
confidence: 99%
“…Empirical and theoretical studies also have identified possible evolutionary pathways to dioecy under these selective forces (reviewed in Barrett, 2002). Transitions to dioecy from distyly (e.g., Darwin, 1877; Barrett and Shore, 1987;Barrett, 1990), from monoecy (e.g., Lloyd, 1980;Renner and Ricklefs, 1995;Renner and Won, 2001;Dorken and Barrett, 2004), and from gynodioecy (e.g., Charlesworth and Charlesworth, 1978a;Ashman, 1999;Charlesworth, 1999;Delph, 2003) have been explored. Despite multiple evolutionary forces and diverse intermediates, these evolutionary transitions all have the same end result-functionally unisexual individuals.…”
mentioning
confidence: 98%
“…Previous phylogenetic analyses of the evolution of gender strategies have been aimed at identifying independent transitions to evaluate the selective mechanisms responsible for gender dimorphism (e.g., Hart 1985;Wagner et al 1995;Weller et al 1995;Soltis et al 1996;Sakai et al 1997;Renner and Won 2001;Levin and Miller 2005). These findings, in conjunction with population-level studies, can support hypotheses that specific ecological factors favor transitions from gender monomorphism to dimorphism (reviewed in Ashman 2006; Barrett and Case 2006).…”
Section: Dynamic Evolutionary History Of Sexual Systems In Wurmbeamentioning
confidence: 88%
“…A number of studies have employed phylogenies to investigate evolutionary transitions in plant reproductive characters (e.g., Weller and Sakai 1999 and references therein; Weiblen et al 2000;Renner and Won 2001;Krahenbuhl et al 2002;Miller 2002;Vamosi et al 2003;Graham and Barrett 2004;Givnish et al 2005;Gleiser and Verdú 2005;Levin and Miller 2005). These studies are primarily aimed at estimating the number of times particular traits arose and/or the ecological or morphological context in which traits may have evolved, which provide indirect evidence of the proximate mechanisms responsible for phenotypic change and the adaptive significance of trait transitions.…”
Section: Introductionmentioning
confidence: 98%